Left-wing economic ideas in the 2001 crisis: Formation of the first critical voices in the political economy of the Socialist Culture Club - Rossi, Ignacio Andrés (2025)
The Socialist Culture Club (CCS) (1984-2008) and the magazine La Ciudad Futura (LCF) were two significant areas of discussion of the so-called democratic left in post-dictatorial Argentina. Renowned intellectuals participated in both spaces, who even coincided in both instances, promoting debate on the political, cultural and economic situation for more than twenty years. This article investigates the economic discussions developed in the Club and in LCF in the context of socioeconomic decomposition of the government of Fernando de la Rúa (1999-2001). The main archival material used were the recorded meetings of the CCS and the LCF articles, focusing on the political-economic debate that took place in parallel in both instances. As could be seen, the economic debate became relevant in the years of the 2001 crisis and given the scarcity of economists in both spaces, specialists were sought to contribute to the debate in this field. Thus, the issue surrounding the economy, considering the critical context that was being experienced, motivated the first questions about the convertibility model in democratic socialism, bringing to debate economic ideas discredited during the nineties such as State intervention, exchange control, industrial insertion, among others.